Rancang Bangun Aplikasi Absensi Siswa Pada SMK Tarbiyah Islamiyah Berbasis Android - Riska Mutia (LPPM Universitas Al Washliyah Labuhanbatu, 2024)
The attendance system is an important thing in a lecture as a student attendance recorder. At SMK Tarbiyah Islamiyah, attendance determines whether a student is entitled or not to take the Semester Final Examination with a percentage of 80% of 16 meetings in one semester. Currently, attendance is done conventionally, where students sign an attendance form based on the subject being studied. Retrieval of attendance data manually has many shortcomings, such as invalid data when the data entered is wrong, missing or corrupted existing data. Sheets of paper that are used as attendance tools are used during the lecture period of one semester, so the paper used is generally easily damaged. The problem with paper media is the background of the need for applications that can handle the attendance process, and at least reduce the level of risk of damage to the attendance data that has been generated. Associated with the problem of attendance files that have a high risk of damage and the ability of mobile devices that are able to process digital files that make it possible to deal with existing attendance system problems, the rationale for making applications that can handle student attendance problems that occur in the world of lectures emerges. The ability of Android as a sophisticated device, is considered very capable of dealing with existing problems. The application that is built is expected to be able to handle data processing in the attendance system so as to produce the required information such as recapitulation data, as well as overcome the problem of attendance data damage.